Pengaruh Harga, Citra Merek, Kualitas Produk dan Gaya Hidup Terhadap Keputusan Pembelian Perlengkapan Bayi Bagi Ibu Milenial - Hilda Puspita Pratyaharani; Suroso, Arif Imam; Ratono, Joko (School of Business, Bogor Agricultural University (SB-IPB), 2022)
A phenomenon that has recently become more and more common is shopping for baby gear product, which is considered by millennial moms as a crucial and primary need within this age group. A purchase decision is a response to purchase decision by considering the product selection, brand selection, channel selection, timing of the purchase selection, and the amount of the money to decide on a purchasing. This study aimed to analyze the impact of price, brand image, product quality and lifestyle on baby gear purchasing decisions for millenial moms. This study used voluntary sampling technique with primary data taken from 125 respondents. The analytical method was conducted using SEM-PLS analysis. The results of the study based on the distribution of respondents' answers showed that the respondents' answers were dominated by agreeable answers to the indicators of each research variable. The hypothesis testing showed that product quality and lifestyle has an impact to the decision to purchase baby equipment for millennial moms. Meanwhile, price and brand image has no impact to the decision to purchase baby equipment products for millennial moms. The strategy that can be suggested for the company is to maintain the quality of the products sold, conduct surveys regarding customer satisfaction regularly, develop products that adapt to current trends, convey detailed information about the products offered, and take advantage of activities such as exhibitions as promotional media. Keywords: baby gear, millenial moms, lifestyle, purchasing decisions, SEM